North America. - Boynton, G. W. (T. G. Bradford, 1838)
This map shows North and Central America and the surrounding areas. Countries and regions are shaded in various colors and labeled. Bodies of water and some geographic features are marked (with relief shown by hachures). Prime meridian: Washington.